2009
DOI: 10.1001/archoto.2009.144
|View full text |Cite
|
Sign up to set email alerts
|

The Hemostatic and Hemodynamic Effects of Epinephrine During Endoscopic Sinus Surgery

Abstract: clinicaltrials.gov Identifier: NCT00852410.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
(37 reference statements)
1
22
2
2
Order By: Relevance
“…De Morais et al found that 1:100,000 compared with 1:200,000 injectable epinephrine had no perceivable impact on hemodynamic status during third molar extraction . However, when looking specifically at endonasal injections prior to ESS, Moshaver et al found that lidocaine with 1:200,000 epinephrine had less of a hemodynamic effect than lidocaine with 1:100,000 epinephrine in a prospective, randomized, controlled trial . In our study we found no significant difference in hemodynamic parameters when comparing 1:100,000 and 1:200,000 concentrations ( p > 0.05), even though both solutions increased blood pressure and HR when compared with baseline.…”
Section: Discussioncontrasting
confidence: 58%
“…De Morais et al found that 1:100,000 compared with 1:200,000 injectable epinephrine had no perceivable impact on hemodynamic status during third molar extraction . However, when looking specifically at endonasal injections prior to ESS, Moshaver et al found that lidocaine with 1:200,000 epinephrine had less of a hemodynamic effect than lidocaine with 1:100,000 epinephrine in a prospective, randomized, controlled trial . In our study we found no significant difference in hemodynamic parameters when comparing 1:100,000 and 1:200,000 concentrations ( p > 0.05), even though both solutions increased blood pressure and HR when compared with baseline.…”
Section: Discussioncontrasting
confidence: 58%
“…10,[12][13][14][15] Although these effects are of significant concern, they are largely the result of intravascular injection and there is limited literature on the safety of topical CE use or the optimal dose. 11,[16][17][18][19] One study concluded that topical CE use was safe in sinus surgery when combined with avoidance in patients with comorbid cardiac disease. 20 An additional practical concern with the use of CE arises from the potential for the masking of arterial bleeding, which may manifest postoperatively after the vasoconstriction has resolved.…”
mentioning
confidence: 99%
“…Zhao et al. also found significant increase in heart rate and significant decrease in blood pressure 1.5 minutes after infiltration of lidocaine with epinephrine . There are several additional reports in the literature on the adverse effects following intranasal preparation for ESS, including several recorded events of significant cardiac morbidity .…”
Section: Discussionmentioning
confidence: 92%
“…Zhao et al also found significant increase in heart rate and significant decrease in blood pressure 1.5 minutes after infiltration of lidocaine with epinephrine. [13][14][15][16] There are several additional reports in the literature on the adverse effects following intranasal preparation for ESS, including several recorded events of significant cardiac morbidity. [17][18][19][20][21] Furthermore, a randomized study by Javer et al called into question the therapeutic value of infiltrated epinephrine, as there was no difference in blood loss during ESS between patients receiving infiltrated 0.25% bupivacaine with 1:200,000 epinephrine and those receiving saline control injections.…”
Section: Discussionmentioning
confidence: 99%